2D3C measurement of velocity, pressure and temperature fields in a intake flow of an air turbine by Filtered Rayleigh Sattering (FRS) and validation with LDV and PIV - Dues, Michael; Dues, Fritz; Melnikov, Sergey; Steinbock, Jonas Johannes; Doll, Ulrich; Röhle, Ingo; Migliorini, Matteo; Zachos, Pavlos K. (International Symposium on the Application of Laser and Imaging Techniques to Fluid Mechanics, 2024)
A Filtered Rayleigh Scattering Technique is implemented in two different experimental setups and compared to the established velocity measurement techniques Laser Doppler Anemometry (LDA) and Particle Image Velocimetry (PIV). The Frequency Scanning Filtered Rayleigh Scattering Method employed uses an imagefiber bundle which allows for the simultaneous observation of the flow situation from six independent perspectives, utilizing only one sCMOS camera. A testrig with a nominal diameter of 80 mm was implemented by ILA R&D GmbH. Here measurements with straight pipe flow and a swirl generator were realised, as well as comparisions with LDA. A second experiment utilized Cranfields University’s Complex Intake Facility (CCITF), enabling the simulation of the flow field for an engine intake as observed behind an S-Duct diffuser. The diameter in the measuring plane was 160 mm. Measurements up to a mach number of 0.4 were performed and compared with HighSpeed Stereo-PIV (S-PIV) measurements. Good agreement was achieved in respect to both the absolute magnitude of the velocity measurements as well as to the resolution of complex flow structures. The developed FRS multi-view Setup is able to simultaneously determine the 3D velocity components, the pressure and the temperature on a measurement plane with high resolution and without seeding. After calibration the FRS system yields the pressure and temperature within 3 percent respectively 0.8 percent of the reference values. The measured velocity was within 1-2 m/s of the reference.
Keywords: FRS; Seeding free; Fiber Optic; LDA; PIV